Identifying Causality Relationship between Energy Consumption and Economic Growth in Developed Countries - DinÃ§er, Hasan; YÃ¼ksel, Serhat; AdalÄ±, Zafer (International Business and Accounting Research Journal, 2017)
The main purpose of this study is to evaluate the causality relationship between energy consumption and economic growth for developed countries. Within this context, annual data of 22 developed countries was examined by using Dumitrescu Hurlin panel causality analysis. As a result, it was determined that that there is a bidirectional relationship between energy consumption and economic improvement for developed countries. This condition provides two different results. Firstly, energy consumption has an influence on economic development for these countries. While considering this result, it can be said that any limitation in energy consumption will restrict economic growth. Moreover, it was also concluded that level of economic growth is the main reason of energy consumption for developed countries. In other words, developed countries tend to have more energy consumption when their economies are growing.